Ultimate Sensitivity of Physical Sensor for Ammonia Gas Detection Exploiting Full Differential 3-Omega Technique. (25th October 2017) - Lotfi, Ardalan; Mahdavifar, Alireza; Struk, Daniel; Stetter, Joseph R; Navaei, Milad; Hesketh, Peter
Abstract : This paper is on the development of physical-based gas sensor for detection of highly toxic and corrosive ammonia. COMSOL simulation was used to study the effects of geometry on sensor sensitivity. The uniform cross-section micro-wire is shown to have the highest sensitivity to the surrounding gas. In order to further improve the sensor sensitivity, 3-Omega technique is combined with a differential electrical measurement. The proposed method enhances the sensor's performance for detection of low concentration gas ammonia in nitrogen, and reaches five hundred ppm for ammonia gas.